Analisis Kepuasan Pelanggan Terhadap Kinerja Layanan Air Bersih Menggunakan Metode TOPSIS (Studi Kasus PDAM Wilayah Pontianak) - Marsela, Dwi; Purnomo, Agus Sidiq (JATISI, 2024)
Regional Drinking Water Company (PDAM) has an important role in providing clean water services for the community. Customer satisfaction is a crucial aspect that needs to be considered to improve PDAM performance. This research aims to analyze customer satisfaction with PDAM performance in Pontianak area and optimize clean water service by using Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method in decision support system. The TOPSIS method is a multi-criteria decision-making method that can evaluate alternatives based on established criteria. Customer satisfaction data will be collected through surveys and processed using the TOPSIS methodology to produce an alternative ranking of service improvements. The results of this study are expected to provide recommendations for PDAM in optimizing performance and improving the quality of clean water services in Pontianak area based on customer preferences